Cafe Brenda Cookbook : Seafood and Vegetarian Cuisine - Langton, Brenda, 1957- (Book collections on Project MUSE., 2004)
This book contains Brenda Langton's most requested recipes, including Miso and Herb Pt, Poached Rainbow Trout, and Burgundy Mushroom Stew. Desserts, like Almond-Hazelnut Tart and Chocolate Carrot Cake, feature reduced amounts of dairy products and natural sweeteners. The Cafe Brenda Cookbook brings the tastiest secrets of one of Minneapolis's best-loved restaurants into your own home.